Analisis Wawasan Mahasiswa Terhadap Baju Adat Yang Ada Di Indonesia - Dita Apriliyani; Rufaidah Kamilia Ahsani; Danda Aditya; Muhammad Dearil Ardiansyah (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Analysis of Students' Insights Regarding Traditional Clothing in Indonesia and Responses Regarding The Differences With These Traditional Clothing and Current Clothing. In relation to national identity in the context of a nation related to culture, Indonesia itself is a country with a variety of ethnic and cultural diversity, where one of the varieties of Indonesian culture is traditional clothing. Traditional clothing is one of Indonesia's cultural treasures whose existence has received praise from many countries in the world. The preservation of traditional clothing needs to continue, one of which is through students as the generation of change in a nation. The aim of this research is to find out the insights of students as the spearhead of the nation's struggle regarding Indonesian traditional clothing. The method used in this research is a qualitative method by collecting data through interviews. The data was analyzed and explained descriptively. The results of the research showed that based on the 10 questions asked, respondents tended to answer not in detail and in depth, apart from that, some answers only stated "don't know" such as the respondent with the initials HD who answered three questions in a row with the answer that he didn't know. The conclusion of this research is that student respondents do not have broad insight regarding traditional clothing, so a change program is needed